A Comparative Study on Amperometric Detection of Urea by Polyaniline and Poly (O-anisidine) Film under Galvanostatic Method - Kiran Paithankar; Priyanka Choudhari; Ritesh Yadav; Suresh More; Dattatraya Galhe; Vikas Gade (Current Topics on Chemistry and Biochemistry Vol. 5, 2022)
The growth mechanism of polyaniline (PANI) and poly (O-anisidine) (POA) on an indium tin oxide (ITO) substrate with the supporting electrolyte HClO4 has been explored. Polyaniline being ecological steady, many scientists covered thing leading polymer by intriguing on the redox properties related with the chain of nitrogen particles. The PANI and POA polymer film that was formed on the indium tin oxide substrate was created using the electrochemical polymerization process under galvanostatic conditions in an aqueous solution with the supporting electrolyte HClO4 at a temperature of 270C. Analytical methods like UV-visible, FTIR, and FE-SEM studies were used to characterise the organised materials in order to compare the amperometric response of PANI and POA film on aurease enzyme in traditional sensor. The performance of developed sensor was evaluated and the obtained urea biosensor exhibited shorter response time (3 s), wider range 1 × 10-9 to 9 ×10-9 M and the detection limit found to be 1 × 10-9 M. About 80 % of enzyme activity is retained for about 40 days. A modified sensor performs better with polyaniline than one with poly (O-anisidine).